The effect of storage temperature on chilli pepper condiment shelf life and quality - Irawan, Adetiya; Sari, Dessy Agustina (AGROINTEK, 2025)
This study investigates the shelf life of Sambal Goang, a popular Indonesian chili pepper-based condiment, under different storage temperatures using the Accelerated Shelf Life Testing (ASLT) method. The increasing demand for chili peppers and the need for effective preservation methods prompted this research. The research stored the samples at 4°C and 30°C, conducting sensory evaluations over 30 days to assess texture, aroma, appearance, and color. Results showed significant quality degradation at 30°C, with rapid mold growth and rancidity. In contrast, samples stored at 4°C maintained better sensory attributes, extending the shelf life to 30 days compared to 24 days at 30°C. The study highlights the critical role of temperature in preserving the quality and extending the shelf life of Sambal Goang, offering practical insights for producers to enhance product safety, reduce waste, and improve economic returns for chili pepper farmers and sambal producers. These findings contribute to the advancement of food preservation strategies, promoting the viability of traditional culinary products in modern markets.